2013
DOI: 10.1186/gb-2013-14-5-r44
|View full text |Cite
|
Sign up to set email alerts
|

Adult monozygotic twins discordant for intra-uterine growth have indistinguishable genome-wide DNA methylation profiles

Abstract: BackgroundLow birth weight is associated with an increased adult metabolic disease risk. It is widely discussed that poor intra-uterine conditions could induce long-lasting epigenetic modifications, leading to systemic changes in regulation of metabolic genes. To address this, we acquire genome-wide DNA methylation profiles from saliva DNA in a unique cohort of 17 monozygotic monochorionic female twins very discordant for birth weight. We examine if adverse prenatal growth conditions experienced by the smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…The observed epigenetic patterns in the discordant twins will be linked to metabolic phenotypes to look for epigenetic modification induced by birth weight discordance and its association with changes in metabolic profiles. Our results will also serve as reliable replicates to the findings of Souren et al (Souren et al, 2013).…”
Section: Twins For Epigenetic Studies Of Human Ageing and Developmentsupporting
confidence: 78%
See 1 more Smart Citation
“…The observed epigenetic patterns in the discordant twins will be linked to metabolic phenotypes to look for epigenetic modification induced by birth weight discordance and its association with changes in metabolic profiles. Our results will also serve as reliable replicates to the findings of Souren et al (Souren et al, 2013).…”
Section: Twins For Epigenetic Studies Of Human Ageing and Developmentsupporting
confidence: 78%
“…In this regard, identical twins discordant for birth weight are ideal subjects for studying the impact of very early life adverse environment on epigenetic regulation of health at adult ages as the genetic part of epigenetic control is cancelled out, enabling pure association between environmental exposure and epigenetic status. Using a small sample of 17 pairs of MZ twins discordant for birth weight, Souren et al (Souren et al, 2013) reported no significant intra-pair differential DNA methylation pattern in a genome-wide analysis. We are currently working on whole-genome DNA methylation data on a relatively large sample of 150 pairs of identical twins discordant for birth weight.…”
Section: Twins For Epigenetic Studies Of Human Ageing and Developmentmentioning
confidence: 99%
“…12 However, these findings have not been reproduced in prospectively collected umbilical cord blood, or placental samples from babies born with growth restriction, or across a range of birth weights investigated in later life. [13][14][15] Furthermore, gestational age at delivery has a powerful effect on fetal and placental methylation status, 16,17 which has not always been considered in earlier studies of FGR offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The effects appeared to be specific to human umbilical vascular endothelial cells, and significant changes were not observed in placental tissue or cord blood mononuclear cells. The second study used Infinium 450K to compare the methylation levels in buccal samples from 17 monochorionic MZ adult twins (Souren et al, 2013). By comparing the methylation differences between the heavy and light co-twins and adjusting the methylation levels with leukocyte subtypes, the authors identified 3,153 birth weight differential methylation sites at p < .01 and 45 of these showed absolute methylation differences greater than 5%, but none of these changes reached genome-wide significance.…”
mentioning
confidence: 99%
“…Several studies in twins have explored epigenetic and gene expression profiles in relation to birth weight or maternal factors strongly associated with birth weight (Gordon et al, 2011Loke et al, 2013;Ollikainen et al, 2010;Souren et al, 2013;Tan et al, 2014). To date, three EWAS have focused on MZ twins discordant for birth weight.…”
mentioning
confidence: 99%